2021
DOI: 10.1186/s12957-021-02426-9
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of arginase-1 and glypican-3 expression levels in patients after surgical intrahepatic cholangiocarcinoma resection

Abstract: Background The aim of this study was to investigate the prognostic value of arginase-1 (Arg-1) and glypican-3 (GPC-3) in patients with intrahepatic cholangiocarcinoma (ICC). Methods Two hundred and thirty-seven patients with ICC were included in this study. All patients had undergone radical surgery and had complete clinical information. Immunohistochemistry was used to assess the levels of Arg-1 and GPC-3 in ICC tissues. Univariate and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Taken together, these findings demonstrated that ARG1 and CPS1 gene alterations might play an essential role in IHCC cancer progression. However, the expression level and prognostic value of ARG1 in IHCC have been comprehensively evaluated [ 20 ]. In addition, arginase-1, encoded by the ARG1 gene, is also considered as a sensitive and specific immunohistochemical marker of normal cells and benign and malignant neoplasms derived from hepatocytes [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these findings demonstrated that ARG1 and CPS1 gene alterations might play an essential role in IHCC cancer progression. However, the expression level and prognostic value of ARG1 in IHCC have been comprehensively evaluated [ 20 ]. In addition, arginase-1, encoded by the ARG1 gene, is also considered as a sensitive and specific immunohistochemical marker of normal cells and benign and malignant neoplasms derived from hepatocytes [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Qiu's 29 study highlights the signi cance of aspartate amination transaminase (AST) to lymphocyte ratio index and CA19-9 level in determining the prognosis of patients with intrahepatic cholangiocarcinoma (ICC). Qiang et al 30 conducted a study on 237 ICC patients who underwent routine resection and used immunohistochemistry to detect glypican-1 and glypican-3. The study found that high expression of glypican-1 and glypican-3 was associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…While healthy adult tissues rarely express GPC-3, it is highly expressed in various solid malignancies, including hepatocellular carcinoma (HCC). 146,147 In ICC tissues, high GPC-3 expression is correlated with shorter DFS and OS. 148 To date, most clinical trials of ACT targeting GPC-3 have focused on HCC.…”
Section: New Targets For Adoptive Cell Therapymentioning
confidence: 99%